Climate change impacts on agriculture's southern frontier – Perspectives for farming in North Patagonia. (31st May 2020) - del Barrio, Ricardo; Fernandez, Eduardo; Brendel, Andrea S.; Whitney, Cory; Campoy, José A.; Luedeling, Eike
Abstract: Winter chill is expected to decrease in many of the suitable growing regions for deciduous trees. Argentinean North Patagonia hosts extensive fruit tree cultivation, which provides an important contribution to both local and global food security. Using historic records from 11 weather stations from North Patagonia, we evaluate the possible impacts of climate change on fruit tree cultivation. We assess winter chill and seasonal heat availability, and the risk of spring frost events based on outputs from 15 Global Climate Models (GCMs) for two Representative Concentration Pathway (RCP) scenarios and two future time periods (represented by central years 2050 and 2085). Metrics were estimated for 47 years of records from the weather stations, as well as typical conditions for 10 past scenarios and 60 future GCM and RCP projections. Scenarios consisted of 100 plausible annual temperature records produced by a weather generator. Results suggest that fruit tree dormancy in Argentinean North Patagonia will not be strongly affected by climate change. Compared to the past, winter chill may only decrease by 9% in the RCP4.5 scenario by 2050 in the northeastern and eastern subregion, while in the central‐south and west the reduction seems unlikely to exceed 6% by the same RCP scenario and year. Our models project stable high growing season heat in the northeastern and eastern regions, and major increases in the south by 2085 in both RCP scenarios. Projections of spring frost events varied between 0 and about 25 hours below 0°C depending on the site. Increasing heat availability may create opportunities for fruit and nut growers to introduce new species and cultivars to the region. Our results provide a basis for planning such introductions and for enabling growers to exploit new opportunities for producing temperate orchard crops beyond their traditional ranges. Abstract : Phenological responses of deciduous trees, such as flower development in apples, depend on temperature‐related processes like the accumulation of winter chill and spring heat. Deciduous fruit trees are widely grown in Argentinean North Patagonia, but their future prospects are unclear. We studied the possible impacts of climate change on metrics that are relevant for the cultivation of deciduous fruit and nut trees. Results showed that winter chill is likely to remain stable in most of the region, while seasonal heat may experience an increase in the near future. This may allow the expansion of growing areas into regions that so far have been too cold for such trees.